miR-210-3p protects against osteoarthritis through inhibiting subchondral angiogenesis by targeting the expression of TGFBR1 and ID4 - Tang, Han; Zhu, Wenrun; Cao, Lu; Zhang, Jin; Li, Juncheng; Ma, Duan; Guo, Changan (Frontiers in Immunology, 2022)
Excessive subchondral angiogenesis is a key pathological feature of osteoarthritis (OA), as it alters the balance of subchondral bone remodeling and causes progressive cartilage degradation. We previously found that miR-210-3p correlates negatively with angiogenesis, though the specific mechanism of miR-210-3p-related angiogenesis in subchondral bone during OA progression remains unclear. This study was conducted to identify the miR-210-3p-modulating subchondral angiogenesis mechanism in OA and investigate its therapeutic effect. We found that miR-210-3p expression correlated negatively with subchondral endomucin positive (Emcn+) vasculature in the knee joints of OA mice. miR-210-3p overexpression regulated the angiogenic ability of endothelial cells (ECs) under hypoxic conditions in vitro. Mechanistically, miR-210-3p inhibited ECs angiogenesis by suppressing transforming growth factor beta receptor 1 (TGFBR1) mRNA translation and degrading DNA-binding inhibitor 4 (ID4) mRNA. In addition, TGFBR1 downregulated the expression of ID4. Reduced ID4 levels led to a negative feedback regulation of TGFBR1, enhancing the inhibitory effect of miR-210-3p on angiogenesis. In OA mice, miR-210-3p overexpression in ECs via adeno-associated virus (AAV) alleviated cartilage degradation, suppressed the type 17 immune response and relieved symptoms by attenuating subchondral Emcn+ vasculature and subchondral bone remodeling. In conclusion, we identified a miR-210-3p/TGFBR1/ID4 axis in subchondral ECs that modulates OA progression via subchondral angiogenesis, representing a potential OA therapy target.